State and development trends of the quality of the population in Uzbekistan - Abdukakhkhorovna, Mukhamedova Sevara (The journal of contemporary issues in business and government, 2021)
The article developed a system of indicators that determine the standard of living of the population of Uzbekistan, scientific proposals and practical recommendations for their calculation. Practical application of the developed scientific proposals and practical recommendations. In the future, Uzbekistan will develop scientific proposals and practical recommendations aimed at improving the living standards of the population through their active use to improve the level and quality of life.